Boats in fields. Uwe Janson’s Peer Gynt (2006) - Thresher, Tanya (Nordlit, 2015)
This article analyses Uwe Janson’s 2006 TV-film adaptation of Peer Gynt. This 81-minute-long film was shot on the island of Usedom in the Baltic Sea and makes extensive use of the landscape in its investigation of identity. The article examines the effects of limiting the geographical space of Peer’s journey of self-discovery and pays particular attention to the symbolic use of boats. It also explores how Janson mirrors the self-reflexivity of Ibsen’s work and maintains the romantic/anti-romantic dichotomy evident in the poetic text.